Reduction of student misconceptions about elements, compounds, and mixtures through the guided inquiry learning model - Dewi, Yuni Candrika; Fikriyah, Aida; Qomaria, Nur; Yamin, Yamin; Hartiningsih, Try (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This research aims to determine the effectiveness of the guided inquiry learning model in reducing student misconceptions about the material of elements, compounds, and mixtures. The research used a descriptive quantitative method using a pre-experimental research design and a one-group pretest-posttest design. The research sample is class VIII-D SMP Negeri 2 Saronggi, with purposive sampling as the sampling technique. The student's misconception was identified using a three-tier diagnostic test. Data collection techniques using tests, questionnaires, observation, and documentation. Based on the result of the research, it can be concluded that (1) The effectiveness of the guided inquiry learning model reduces student misconceptions about the material of elements, compounds, and mixtures by testing the hypothesis obtained Asymp. Sig < 0,05 (0,00 < 0,05), (2) the guided inquiry learning model can reduce student misconception from an average of 51,92 to 18,46, (3) the implementation of learning of the guided inquiry learning model obtained a percentage of 93% with a perfect category, (4) student responses to guided inquiry learning model is very good with a percentage 80%.